Impact of Difficulties Faced by Adolescents in Making Career Decision on their Mental Health - Khan, Ayesha; Rehman, Adeela (Journal of Education and Vocational Research, 2019)
This research aimed to explore the impact of difficulties faced by adolescents in making a career decision on their mental health. The objective of the research was to explore the factors affecting career decision making and to explore the psychological effect of career decision making difficulties. A quantitative research design was used to collect data through online survey by random sampling method in which a sample of 70 adolescents aged between 18-24 both male (28) and female (42) were collected from Rawalpindi, Pakistan and then analyzed on SPSS. A correlation (p: .002) was found between career indecisiveness and mental health. Independent T test result suggested that gender difference exists with respect to career indecisiveness indicating a value of p to be .01, while one way ANOVA indicated a value of p to be .382, showing that no significant difference exist with respect to respondents age. A chi square result indicated the factors affecting career decision making to be parental (p: .000) and peer pressure (p: .002) and indicated that career decision making time period is stressful for adolescents who feel difficulty in making a career decision (p: .000) indicating a psychological effect. Thus, the hypothesis was proved that adolescents face career decision making difficulties which negatively impact their mental health and it is recommended that they should be given career guidance to help them out in exploring what they really want to do in their lives instead of making a wrong career and regretting it later.